Investigação sobre conservadorismo: uma análise bibliométrica - Maia, V. (2018)
Conservatism is defined in two ways: conditional and unconditional. The conditional conservatism is a result of the asymmetric registration of "good news" and "bad news" and the unconditional conservatism relates to accounting standards discretionarity.In this context, the main objective of this study is to describe and analyze the process of accounting research onconservatism, from 2008 to 2018, based on a bibliometric approach. The present study is essential to complement this knowledge.Findings confirm that accounting research on conservatism is scant. Although in recent years a progressive advance and a strong interest have been demonstrated. However, there is a greater interest in research on conditional conservatism and a small number of proposed measures on unconditional conservatism. However, this topic still represents an area that deserves to be explored in the accounting literature.